Pemberdayaan Perempuan Dalam Produksi Masker Dan Penerapan Disiplin Memakai Masker Bagi Pekerja Harian Dalam Penanganan Wabah Covid-19 - Wiwit Probowati; Nosa Septiana Anindhita (LPPM UMRI, 2021)
The Covid-19 outbreak that hit globally had amajor impact on economic activity in developing countries, especially Indonesia. In order to continue carrying out daily activities, especially working, it is necessary to comply with health protocol. Health protocols when doing activities include wearing masks, washing hands frequently with soap, avoiding crowds and maintaining a minumum distance of 1.5 meters from each other. The need for masks that are currentky not fulfilled by daily workers or laborers in Margomulyo village, Seyegan sub-district, Sleman regency, Province of Yogyakarta is primary need while working. The importance of education regarding the dangers of transmission of the Corona Virus or SARS-Cov-2 needs to be done to prevent the faster transmission of the virus. Therefore, the organization group ‘Aisyiyah in collaboration with Universitas ‘Aisyiyah Yogyakarta, empowers women tailors in neighborhood to produce cloth masks. Furthermore, these mask were distributed to daily workers in the Mrgomulyo village environment who had high mobility and had ahigh potential to transmit the Corona virus.